COMPARATIVE STUDY OF CLINICAL EFFECTIVENESS OF LURIA-NEBRASKA NEUROPSYCHOLOGICAL BATTERY, EEG AND CT SCAN IN BRAIN DAMAGED PATIENTS - James, M.X. (Medknow Publications, 1997)
The clinical effectiveness and concurrent validity of Luria-Nebraska Neuropsychological Battery (LNNB) was assessed in a sample of 30 brain-damaged and 30 non-patient, normal control subjects. Both the groups were matched for age, sex and education. There were highly significant differences between the mean scale scores of the two groups on all LNNB clinical scales. Brain damaged patients did poorer than normal controls. The LNNB had a hit rate of86.66% in diagnosing brain-damaged patients in comparison to 70% and 52% of EEG and CT scan respectively. The three measures were found to be significantly correlated with each other. The LNNB was found to be an effective instrument for neuropsychological assessment.